School Leaders’ and Teachers’ Perspective on Leadership Styles and Decision-Making: Basis for Teachers’ Training Program - Aguilar, Maria Josefina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined school leaders’ and teachers’ perspectives on leadership styles and decision-making as basis for a teachers’ training program in public and private schools in Danao City during the 2025–2026 school year. Anchored on Distributed Leadership Theory, Transformational Leadership Theory, Participative Decision-Making Theory, and Republic Act No. 9155, the study used a quantitative descriptive-comparative design. Data were gathered through a structured questionnaire adapted from the Leadership Style Questionnaire by Northouse and the Decision-Making Questionnaire by Lizzaraga et al. The respondents were 30 school leaders and 353 teachers. Findings showed that authoritarian, democratic, and laissez-faire leadership styles were all evident in the school setting, but teachers consistently perceived these leadership behaviors more strongly than school leaders themselves. Significant differences were found between school leaders’ self-perceived leadership styles and teachers’ perceptions across the three leadership styles. In contrast, no significant differences were found in decision-making perceptions across task, subjective, and context factors, indicating shared understanding of decision-making practices. The study concludes that while leadership styles are experienced differently, decision-making practices are generally aligned, transparent, and commonly understood. It recommends active feedback, consultative meetings, leadership development programs, stronger teacher participation, and a leadership training program to improve participative decision-making. The study supports SDG 4, SDG 16, and SDG 17 by promoting quality education, collaborative school governance, and institutional partnerships. Its sustainability impact lies in strengthening educational, institutional, and governance sustainability through reflective leadership, teacher empowerment, and shared decision-making.
Keywords: Authoritarian Leadership; Decision-Making; Democratic Leadership; Laissez-Faire Leadership; Leadership Styles; School Leaders; Shared Governance; Teacher Participation; Teachers’ Training Program